Marketplace and Digital Marketing Furniture Sales Solutions in the Contemporary Age - Jajang Jajang; Lisa Amalia (Jurnal PKM Manajemen Bisnis, 2022)
Problems in the business world are very complex and difficult to predict. In the last 3 years, global scale problems have emerged, starting from the pandemic, the wars between Russia and Ukraine, and the energy crisis in the western region. It is not imaginable that many companies have gone out of business, because they were unable to face the global economic storm. Not to mention the unstable domestic conditions, starting from high political temperature, the level of unfair business competition, and declining people's purchasing power are a number of problems that need to be addressed. Therefore, the presence of an online market, which is called a marketplace, is one solution to this condition. However, to be able to enter the online market, knowledge is needed, namely digital marketing. This service activity is carried out as one of the efforts of the campus community to be able to contribute to problems in society, namely by providing training on marketplaces and digital marketing. This activity was carried out at furniture SMEs in the Cirebon area with a total of 30 participants. The activity method is carried out by means of training in creating online stores in marketplaces and creating digital advertisements, both on social media and marketplaces. This activity was quite well received and the participants participated enthusiastically. The participants gained knowledge about marketing their furniture products throughout Indonesia by creating an online shop. Then the participants gained knowledge about making advertisements and advertising on social media, both paid and free. With this training, it is expected to increase sales and income, thereby increasing the welfare of the furniture business community in the Cirebon area.